An embodied and ecological approach to skill acquisition in racecar driving - Ziv, Gal (Frontiers in Sports and Active Living, 2023)
Racecar driving is a fast-paced sport that presents the driver-athlete with many perception-action coupling and decision-making challenges. One question that arises is how racecar drivers deal with the influx of perceptual information and manage to perform successfully in such high speeds and, as a result, very limited time to make decisions and act upon them. In this perspective paper, I suggest that the ecological approach is one theoretical framework that can help researchers understand how skill is acquired in racecar driving. I also suggest that an embodied perception of affordances can provide a good basis for research in the field. Specifically, it is an extended embodied cognition that includes not only the driver’s mind and body, but the car itself. In a sense, the driver and the car are embodied into one unit and any perception of affordances should be based on this unit. This paper will also discuss the constraints during a race, the affordances the race driver must perceive and how they change over the course of a race, and how researchers can use a racecar driving paradigm to study human perception and action from an embodied and an ecological approach. Specifically, because the driver is seated, measuring EEG and eye movements is relatively simple and can provide additional information on drivers’ visual perception of affordances, and their ability to act upon them.